Multifactorial resistance mechanisms associated with resistance to ceftazidime-avibactam in clinical Pseudomonas aeruginosa isolates from Switzerland - Baharak Babouee Flury; Baharak Babouee Flury; Baharak Babouee Flury; Anja Bösch; Anja Bösch; Valentin Gisler; Valentin Gisler; Adrian Egli; Salome N. Seiffert; Oliver Nolte; Jacqueline Findlay (Frontiers in Cellular and Infection Microbiology, 2023)
BackgroundIncreasing reports of multidrug resistance (MDR) in clinical Pseudomonas aeruginosa have led to a necessity for new antimicrobials. Ceftazidime-avibactam (CZA) is indicated for use against MDR P. aeruginosa across a broad range of infection types and particularly those that are carbapenem resistant. This study sought to determine the molecular mechanisms of CZA and imipenem (IPM)-resistance in clinical P. aeruginosa isolates obtained from Swiss hospitals.MethodsClinical P. aeruginosa isolates were obtained from inpatients in three hospitals in Switzerland. Susceptibility was determined by either antibiotic disc testing or broth microdilution according to EUCAST methodology. AmpC activity was determined using cloxacillin and efflux activity was determined using phenylalanine-arginine β-naphthylamide, in agar plates. Whole Genome Sequencing was performed on 18 clinical isolates. Sequence types (STs) and resistance genes were ascertained using the Centre for Genomic Epidemiology platform. Genes of interest were extracted from sequenced isolates and compared to reference strain P. aeruginosa PAO1.ResultsSixteen different STs were identified amongst the 18 isolates in this study indicating a high degree of genomic diversity. No carbapenemases were detected but one isolate did harbor the ESBL blaPER-1. Eight isolates were CZA-resistant with MICs ranging from 16-64 mg/L, and the remaining ten isolates had either low/wildtype MICs (n=6; 1-2 mg/L) or elevated, but still susceptible, MICs (n=4; 4-8 mg/L). Ten isolates were IPM-resistant, seven of which had mutations resulting in truncations of OprD, and the remaining nine IPM-susceptible isolates had intact oprD genes. Within CZA-R isolates, and those with reduced susceptibility, mutations resulting in ampC derepression, OprD loss, mexAB overexpression and ESBL (blaPER-1) carriage were observed in various combinations and one harbored a truncation of the PBP4 dacB gene. Within the six isolates with wildtype-resistance levels, five had no mutations that would affect any antimicrobial resistance (AMR) genes of interest when compared to PAO1.ConclusionThis preliminary study highlights that CZA-resistance in P. aeruginosa is multifactorial and could be caused by the interplay between different resistance mechanisms including ESBL carriage, increased efflux, loss of permeability and derepression of its intrinsic ampC.